The Effect of Willingness to Pay on Customer Preferences for Health Insurance Membership: A Systematic Review - Vivilia Dian Mustikasari; Ayu Nur Malasari; Thinni Nurul Rochmah; Kantrey Sugiarto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The community's access to healthcare services is ensured by health insurance, which is a critical element in health finance. Insurance for health can shield you from expensive medical bills that can strain family's budget. This systematic review intended to examine customer preferences for health insurance membership based on their willingness to pay. Four electronic databases served as the information's sources (ScienceDirect, Pubmed, Scopus, and Proquest). The PECOS Framework approach and certain keywords and synonyms were utilized in the search strategy to find publications published between 2011 and 2023. The data extraction, data synthesis, and deductive analysis were carried out on sixteen papers that matched the eligibility requirements. The findings demonstrated that customer preferences for health insurance membership are influenced by willingness to pay, with criteria including education, income, and medical history having a favorable impact. Health insurance managers must be aware of the variables that influence willingness to pay in order to increase membership coverage.